Quantitative risk assessment of industrial accidents for stow net fishermen - Seung-Hyun Lee; Su-Hyung Kim; Kyung-Jin Ryu; Yoo-Won Lee (Fisheries and Aquatic Sciences)
This study quantitatively assessed industrial accident risks among stow net fishmen using Bayesian network analysis. A total of 1,193 fishermen compensation insurance approval records for stow net fishery from 2018 to 2022 were analyzed. A chi-square test revealed different risk factors for coastal and offshore operations. In coastal fishing, rank, work process, and environmental causes were significant predictors of accidents, with fishermen facing four times the risk compared to captains. The risk during fishing was much higher than sailing, maintenance, and catch unloading. Fishing gear-related accidents were more likely than those caused by hull, machinery, and environmental causes. In offshore fishing, the highest risk was observed among fishermen aged 50–60, with South Korean fishermen being 15.26 times more at risk than foreign fishermen. Accidents during fishing were most common, with hull-related incidents far outnumbering those caused by fishing gear, machinery, and environmental causes. These findings provide a quantitative risk assessment of major hazards in stow net fishery, offering insights for targeted risk mitigation strategies.